Down with the Senate? Understanding Support for the Abolition of the Senate in Canada. - Rancourt, Marc-Antoine; Déry, Axel; Poirier, William; Dufresne, Yannick (American Review of Canadian Studies, 2023)
Various governments have debated the question of whether the Canadian Senate should be abolished or reformed since 1980, yet a solution has still not been found. While some advocate for a substantial reform of the institution, others propose to get rid of it completely. Drawing from the 2021 Canadian Election Study, this article explores the underlying value systems that shape opinions on the abolition of the Canadian Senate. The findings suggest that support for the abolition of the Canadian Senate should be understood as part of a set of populist attitudes, the extent of political interest, political knowledge, and party identification.